A randomised controlled trial of high vs low volume initiation and rapid vs slow advancement of milk feeds in infants with birthweights ≤ 1000 g in a resource-limited setting. (1st October 2016) - Raban, Shukri; Santhakumaran, Shalini; Keraan, Quanitah; Joolay, Yaseen; Uthaya, Sabita; Horn, Alan; Modi, Neena; Harrison, Michael
Abstract : Background: Optimal feeding regimens for infants ≤ 1000 g have not been established and are a global healthcare concern. Aims and objectives: A controlled trial to establish the safety and efficacy of high vs low volume initiation and rapid vs slow advancement of milk feeds in a resource-limited setting was undertaken. Methods: Infants ≤ 1000 g birthweight were randomised to one of four arms, either low (4 ml/kg/day) or high (24 ml/kg/day) initiation and either slow (24 ml/kg/day) or rapid (36 ml/kg/day) advancement of exclusive feeds of human milk (mother's or donor) until a weight of 1200 g was reached. After this point, formula was used to supplement insufficient mother's milk. The primary outcome was time to reach 1500 g. Results: infants were recruited (51: low/slow; 47: low/rapid; 52: high/slow; 50: high/rapid). Infants on rapid advancement regimens reached 1500 g most rapidly (hazard ratio 1.48, 95% CI 1.05–2.09, P =0.03). The rapid advancement groups also regained birthweight more rapidly (hazard ratio 1.77, 95% CI 1.26–2.50, P =0.001). There was no apparent effect of high vs low initiation volumes but there was some evidence of interaction between interventions. There were no significant differences in other secondary outcomes, including necrotising enterocolitis, feed intolerance and late-onset sepsis. Conclusions: In this small pilot study, higher initiation feed volumes and larger daily increments appeared to be well tolerated and resulted in more rapid early weight gain. These data provide justification for a larger study in resource-limited settings to address mortality, necrotising enterocolitis and other important outcomes.